2011
DOI: 10.1111/j.1523-5378.2010.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Antigen for Diagnosis of Helicobacter pylori Infection in Stool of Adult and Children

Abstract: Using of AhpC antigen for diagnosis of H. pylori infection is a useful noninvasive method, accurate in adolescents and children, and can be used for the development of a stool antigen detection kit for H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…It has been reported that detection of H. pylori antigens in stool is a suitable noninvasive method for clinical and epidemiologic studies (Koletzko, 2005; Pourakbari et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that detection of H. pylori antigens in stool is a suitable noninvasive method for clinical and epidemiologic studies (Koletzko, 2005; Pourakbari et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
“…HpSA is another non-invasive method with acceptable sensitivity and specificity for clinical and epidemiologic studies that its use has increased in recent years. 19 In this study we estimated the accuracy of HpSA for detecting H. pylori infection and observed that HpSA had sensitivity, specificity, PPV, NPV and accuracy of 96.67%, 93.33%, 93.55%, 96.55% and 95.00%, respectively.…”
mentioning
confidence: 96%
“…8 Epidemiologic studies showed that H. pylori affects over 50% of the world's population, infecting 40% to 50% of the population in industrialized countries and 70% to 90% in developing countries. 10 Invasive tests include endoscopy with gastric biopsy specimens, whereas noninvasive tests include serology, the urea breath test, the stool antigen test, and the polymerase chain reaction test (PCR). Several invasive and noninvasive diagnostic tests are used for the detection of H. pylori infection.…”
mentioning
confidence: 99%
“…12 The culture and identification of the organism is time-consuming but advantageous in that antibiotic susceptibility tests can be conducted. 10 Antigen detection in stool is an attractive noninvasive method that seems very suitable for clinical and epidemiologic studies as it can diagnose active infection in human fecal samples. 13 Nowadays, there is increasing interest in noninvasive methods to diagnose H. pylori infection.…”
mentioning
confidence: 99%